Pengaruh tingkat energi penyinaran terhadap sifat optik pusat warna F-center pada kristal LiF menggunakan spektrometer Uv-Vis (The effect of irradiation energy level on the optical properties of the F-center color center on the LiF crystal using a Uv-Vis spectrometer) - Qerzi Elsadola; - Ratnawulan; - Hidayati (PILLAR OF PHYSICS, 2015)
The phenomenon of color centers in the crystal has been used in various fields, one of which is the imaging plate. Imaging plate is a sheet that can capture and store the information carried by the X-ray. The base material of this imaging plate is alkali halide crystals. Imagine Plates widely used in hospitals for X-ray. To maximize the results of X-ray readings, required a large absorption. This research was done by varying the energy of radiation used. The purpose of this study was to observe the effect of the energy radiation to the optical properties of F-center in LiF crystals and determine how the time effect on the value of the LiF crystals concentration. Optical properties related to the nature of light and the interaction of light with materials. The optical properties were observed in this research is the absorption coefficient and concentration of color centers. Value of the F-center absorption coefficient obtained for the variation of time of 1 hour, 2 hours and 3 hours for 50 keV, 60 keV, 70 keV, 80 keV and 90 keV. Based on result of the research  revealed that the greater the absorption, the concentration will also increase